2020
DOI: 10.1001/jamainternmed.2020.2904
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Strength of Evidence of COVID-19 Studies Registered on ClinicalTrials.gov

Abstract: The coronavirus disease 2019 pandemic has led to a massive activation of clinical research. The methodological strength of these studies is not well characterized but has implications for the quality of evidence produced. We evaluated the characteristics and expected strength of evidence of COVID-19 studies registered on ClinicalTrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 3 publications
1
54
0
4
Order By: Relevance
“… 66 The situation is unlikely to change in the near future, as a review of ClinicalTrials.gov has identified a concerningly large proportion of studies with an expected low level of evidence. 67 Accordingly, a recent systematic review which examined 42 guidelines related to COVID-19 released in the spring/summer of 2020 found that the quality of all was poor, especially with respect to the rigour of their development. 68 The infodemic in scientific literature may result in a churn of studies that capture attention, but do not, and, arguably, should not, contribute meaningfully to clinical practice.…”
Section: The Infodemicmentioning
confidence: 99%
“… 66 The situation is unlikely to change in the near future, as a review of ClinicalTrials.gov has identified a concerningly large proportion of studies with an expected low level of evidence. 67 Accordingly, a recent systematic review which examined 42 guidelines related to COVID-19 released in the spring/summer of 2020 found that the quality of all was poor, especially with respect to the rigour of their development. 68 The infodemic in scientific literature may result in a churn of studies that capture attention, but do not, and, arguably, should not, contribute meaningfully to clinical practice.…”
Section: The Infodemicmentioning
confidence: 99%
“…Understanding the cardiovascular response to SARS-CoV-2 re-infection and Influenza infection will be a particularly important area of research given the common theme in cardiovascular diseases, disorders and conditions of a "second hit phenomenon" that can accelerate pathological abnormalities and lead to clinical events. The bar must be set high to assure that research undertakings meet the vigorous standard needed to inform and advance the field [53].…”
Section: Research Platformsmentioning
confidence: 99%
“…However, efforts to date have not managed to avoid research waste and ensure that all relevant studies contribute to the formulation of guidance and decisions in practice and policy 25. Most studies on covid-19 treatments have methodological limitations (eg, small samples and diverse designs and outcomes) 26. A sizeable portion of studies, collectively including thousands of patients, may therefore have little prospect of adding to the growing evidence base on efficacy.…”
Section: Progress On Research Coordination and Collaborationmentioning
confidence: 99%